2021
DOI: 10.1002/er.6490
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric, quantum efficiency and photovoltaic properties in perovskite BiFeO 3 thin films: First principle calculations and Monte Carlo study

Abstract: Summary Monte Carlo simulations and the full‐potential linearized augmented plane wave (FP‐LAPW) method in the framework of density functional theory (DFT) are applied to investigate the quantum efficiency, ferroelectric, and photovoltaic properties. We have used the generalized Perdew Burke Ernzerhof gradient approximation (PBE‐GGA) as well as the Becke‐Johnson modified exchange potential (TB‐mBJ) to correct the gap's energy. The gap energy results of 2.5 eV obtained using mBJ are reasonable compared to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…A similar idea was attempted using Procedure A. However, equation ( 16) does not show the same nature as the one just described for equation (17), 𝑖.𝑒., that a single root is easily observed when plotting 𝑚 𝑅𝑠ℎ vs. 𝐼 𝑠𝑎𝑡 . This can be seen, for example, in Fig.…”
Section: Theoretical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A similar idea was attempted using Procedure A. However, equation ( 16) does not show the same nature as the one just described for equation (17), 𝑖.𝑒., that a single root is easily observed when plotting 𝑚 𝑅𝑠ℎ vs. 𝐼 𝑠𝑎𝑡 . This can be seen, for example, in Fig.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Other techniques are Procedure A and Procedure B proposed in [2] , [16] . Finally, other methods are based in Monte Carlo simulations, artificial neuronal networks, non-linear least-squares method, exponential model, or ab initio calculations [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] . A review of the limitations and assumption validity of these main techniques can be found in [27] .…”
Section: Introductionmentioning
confidence: 99%
“…Also there, a summary of the available techniques to obtain them is described. Briefly, a myriad of methods can be found in the literature, based in Monte Carlo simulations, artificial neuronal networks, non-linear least-squares method, exponential model, or ab initio calculations [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] . It is worth mentioning here the study by Khan et al, where they reviewed the limitations of these main techniques [16] .…”
Section: Introductionmentioning
confidence: 99%
“…About ferroelectric/ferrimagnetic materials both physical mechanism of thin films and potential applications in electronic devices were investigated. [16][17][18][19][20][21][22][23][24] Meanwhile, lead titanate (PbTiO 3 ) is a capable ferroelectric compound and has been applied in various fields for instance nonvolatile memories, transducers, and actuators because of their excellent electrooptic, sensors, and piezoelectric possessions. 25 Besides, one of the metal organic frameworks (MOF) is copper phthalocyanine (CuPc) that has been recognized as a metal-organic photosensitizer material.…”
Section: Introductionmentioning
confidence: 99%
“…For compaction of an electronic device, a thin film based on the composite is an essential component of multifunctional resources. About ferroelectric/ferrimagnetic materials both physical mechanism of thin films and potential applications in electronic devices were investigated 16‐24 . Meanwhile, lead titanate (PbTiO 3 ) is a capable ferroelectric compound and has been applied in various fields for instance nonvolatile memories, transducers, and actuators because of their excellent electrooptic, sensors, and piezoelectric possessions 25 .…”
Section: Introductionmentioning
confidence: 99%